Penggunaan Ungkapan Basa Basi dalam Bahasa Jepang - Andry Anita Dewi, Ni Made; Ari Sulatri, Ni Luh Putu (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 18 No 1 (2018), 2018)
Japanese society in everyday life cannot be separated from relations of communication between members of the community itselft. Based on the phenomenon of the society, it can be ascertained that courtesy is the most important thing in it. For that reason, the Japanese society functioning courtesy to achieve a good and communicative speech. The purpose of this study is to describe and analyze the functions of courtesy attached that contained in Japanese speech based on the theory of functions proposed by Leech. The data used in this study is novel titled Beautiful Life by Eriko Kitagawa. Some functions of courtesy such inhibitions were found in this study is to express a greeting, excited feelings, prise and offering something.